STRATEGI PENGELOLAAN RUANG KOTA UNTUK MENDORONG AKTIVITAS EKONOMI : SUATU KAJIAN STUDI LITERATUR (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The rapid growth of urban areas has increased the complexity of ur- ban spatial management, directly influencing the dynamics of eco- nomic activities. This study aims to examine various urban space management strategies that effectively stimulate urban economic growth through a literature review. The method employed is a litera- ture study analyzing scholarly sources from the last five years. The findings indicate that the integration of spatial planning, infrastruc- ture development, functional zoning, and participatory approaches from communities and stakeholders are key strategies for fostering economically productive urban spaces. Furthermore, adaptive spatial management responsive to social and technological changes is also a critical success factor. The study concludes that collaborative and sustainable approaches are essential in managing urban spaces to build inclusive and dynamic economic ecosystems.